Effects of gastrointestinal hormones on the growth of human intestinal epithelial cells in vitro. Issue 5 (May 1989) - Simopoulos, C; Gaffen, J D; Bennett, A
Abstract : The growth of cultured epithelium like cells from human normal embryonic intestine was studied in response to various hormones using a method that quantifies the number of cells by the amount of dye that they bind after fixation. Gastrin and neurotensin in the pg/ml range and higher caused small increases in cell growth. Glucagon and VIP were stimulatory in the low ng/ml range, whereas somatostatin and bombesin had no effect at the lower concentrations but were stimulatory at the highest concentration tested (10 and 100 ng/ml respectively). Secretin and pancreozymin (cholecystokinin) seemed to be ineffective.